2022
DOI: 10.33448/rsd-v11i10.32582
|View full text |Cite
|
Sign up to set email alerts
|

Trans-anethole, the major constituent of the essential oil of anise, improves the antiarthritic effects of methotrexate in rats

Abstract: The aim of this study was to evaluate the effect of trans-anethole in combination with methotrexate, compared to monotherapy with trans-anethole or methotrexate, on inflammatory parameters and oxidative stress of arthritic rats. The experimental model of arthritis induced by Freund's complete adjuvant (AIA) in rats was used. Treatment with trans-anethole and methotrexate, in combination or monotherapy, was started on the day of AIA induction and continued for 21 days. The association of anethole (62.5 mg/Kg) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In this context, we assessed the effects of P. anisum as a protective agent against PCOS damage on these markers in a rat PCOS model. Many studies have reported that P. anisum has great potential as an antioxidant and anti-inflammatory factor due to the presence of phytochemical compounds (e.g., flavonoids and trans-anethole) responsible for the medicinal properties of this plant ( 43 - 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we assessed the effects of P. anisum as a protective agent against PCOS damage on these markers in a rat PCOS model. Many studies have reported that P. anisum has great potential as an antioxidant and anti-inflammatory factor due to the presence of phytochemical compounds (e.g., flavonoids and trans-anethole) responsible for the medicinal properties of this plant ( 43 - 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this combination therapy allowed for a reduction in the methotrexate dosage, mitigating the potential side effects associated with high-dose methotrexate treatment. 24 While anethole shows promise in mitigating the detrimental effects of RA, the precise mechanism underlying its anti-arthritic properties in RA remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…One notable study has demonstrated that a combination therapy involving anethole and the anti‐arthritis drug methotrexate effectively attenuated oxidative stress and inflammation associated with arthritis. Importantly, this combination therapy allowed for a reduction in the methotrexate dosage, mitigating the potential side effects associated with high‐dose methotrexate treatment 24 . While anethole shows promise in mitigating the detrimental effects of RA, the precise mechanism underlying its anti‐arthritic properties in RA remains unclear.…”
Section: Introductionmentioning
confidence: 99%